ISOLASI DAN AKTIVITAS PLANT GROWTH PROMOTING RHIZOBACTERIA (RHIZOBIUM, AZOSPIRILLUM, AZOTOBACTER, PSEUDOMONAS) DARI TANAH PERKEBUNAN KARET, LAMPUNG - Sri Widawati (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Analysis of phosphate dissolving activity, P dissolved; PMEase and IAA production by Plant Growth Promoting Rhizobacteria group(PGPR)is a parameter to determine the effectiveness of these bacteria as biological organic fertilizer (BOF).This study was aimed to obtain PGPR (Rhizobium, Azospirillum, Azotobacter, Pseudomonas) that were potential as a BOF to reclamation on degraded plantation area. This study used a random sampling method for 11 sampling points (1999P1, 1999P2, 1999P3, 1999P4, 1999P5, 2007P, 2007P1,2007P2, 2007P3, 2007P4, 2007P5) in the area of rubber plant roots.Isolation and counting of bacterial populations used plate count method on selective media (YEMA, Okon, Caceres, NFB AMA, PAB) whereas phosphate dissolving activity analysis, Dissolution Efficiency Index (DE), PMEase and IAA production following the method of Nguyen, Bray, Seshadri, Tabatabai, and Gravel.The results showed that of the 11 sampling points, 11 isolates were obtained effectively consisting of four groups of bacteria, namely: Rhizobium,5 5 5 5 Azospirillum, Azotobacter and Pseudomonas with the number of population: 3.3x10 , 80x10 , 20x10 , and 14x10 cfu.The results of the analysis of DE, soluble P, PMEase acid-base, and the highest IAA obtained from the bacterium isolated from the sampling point 1999P3 and 1999P1. This potential isolates will be used to the next research on reclamation of degraded land plantation